Transforming waste into valuable resources: Recycled nitrile-butadiene rubber scraps filled with electric arc furnace slag - Anna Gobetti; Giovanna Cornacchia; Giorgio Ramorino (Cleaner Engineering and Technology)
This study investigates the valorization of two industrial waste streams - nitrile butadiene rubber (NBR) scraps and electric arc furnace (EAF) slag – in the development of recycled NBR compounds filled with EAF slag as filler. A new recycling method for NBR scraps is employed via calendering at room temperature without the need for curatives, chemical agents, or pre-grinding. The resulting recycled NBR is then used as a matrix for EAF slag particles to produce sustainable rubber compounds that are entirely recycled. Characterization reveals that incorporating EAF slag enhances the devulcanization process of recycled NBR during recycling. The filler grain size affects composite properties like hardness, crosslink density, and tensile modulus, with finer slag particles (<50 μm) exhibiting improved reinforcement due to increased interaction surface with the rubber matrix. Dynamic mechanical analysis indicates that recycled NBR filled with EAF slag exhibits a more significant Payne effect compared to unfilled recycled NBR, due to filler-matrix interactions. Interestingly, EAF slag facilitates the rapid fractional recovery of the low-strain storage modulus after experiencing high-amplitude strain, ascribed to the formation of a rigid rubber layer around the slag particles.Overall, the findings highlight the potential to valorize these two waste materials effectively by producing functional recycled NBR/EAF slag composites with desirable properties through a simple, industrially viable recycling method without capital-intensive equipment. This represents both environmental and economic benefits through waste valorization and industrial symbiosis.